A non‐incremental solution procedure for elastoplastic problems in structural mechanics. Issue 1 (14th December 2021) - Bamer, Franz; Shirafkan, Nima; Cao, Xiaodan; Oueslati, Abdelbacet; Stoffel, Marcus; De Saxcé, Géry; Markert, Bernd
Abstract: In this contribution, we present a non‐incremental solution procedure for the efficient treatment of elastoplastic problems. To this end, all time history data are decoupled into space and time, and the solution is obtained using the fixed‐point algorithm.